Vita Sancti Servani and Vita Sancti Kentigerni : [Lives of St Sert and St Kentigern/ Mungo] - Jocelin, active 1200; Jocelin of Glasgow Bishop died 1199; Hollington, Josias, active 1650; [Sumner], Mr active c 1650; Armar, William
Towards the end of the twelfth century Bishop Jocelin of Glasgow commissioned Jocelin of Furness to write this Life of Kentigern. Its opening 12 pages are Jocelin of Furness' Life of St Serf, Kentigern's master.
Previous numbers G4.4.7; V3.4.16.
Rubricated and green initials. Later annotations and manicules added. Pages (and some annotations) have been cut. Names written inside front cover and on title page: Josias Hollington; Mr Sumner and Wm. Armar.
Some leaves have flay holes and all have visible rulings.
Marsh's Library stamp on first page.
See 'Fragments from Scotland of the Acta of a General Chapter' by Henry Hargreaves in Archivum Fratum Praedicatorum Vol LXI, 1991 and 'Vita Sancti Servani: The Life of St Sert' in The Innes Review, Vol XLIV, Autumn 1993 (Z4.5.5(1)).
Facsimile and translation available Z4.5.21a.
Keywords: Kentigern, -- Saint, -- -approximately 612; Servanus, -- Saint, -- active 5th century-6th century; Manuscripts, Medieval